2008
DOI: 10.1111/j.1540-6210.2007.00864.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Use of Performance Data to Improve Municipal Services: Evidence from the North Carolina Benchmarking Project

Abstract: Many local governments measure and report their performance, but the record of these governments in actually using performance measures to improve services is more modest. The authors of this study examine patterns of performance measurement use among a set of North Carolina cities and conclude that the types of measures on which officials rely, the willingness of officials to embrace comparison, and the degree to which measures are incorporated into key management systems distinguish cities that are more like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
187
0
14

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(208 citation statements)
references
References 40 publications
7
187
0
14
Order By: Relevance
“…Various measures that track the availability of performance information have been found to be positively associated with use ( Melkers and Willoughby (2005) find that the availability of measures in budget documents actually reduces the influence of these measures in the budget process and suggest that this may be the result of information overload. Ammons and Rivenbark (2008) point out that it is not only the existence of measures but also the ability to tie these measures to management systems that fosters use. We test whether the perceived availability of measures and the linkage of these measures to management processes (via benchmarking, strategic planning, customer service measurement, and linking to budgets) are associated with performance information use.…”
Section: Organizational Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various measures that track the availability of performance information have been found to be positively associated with use ( Melkers and Willoughby (2005) find that the availability of measures in budget documents actually reduces the influence of these measures in the budget process and suggest that this may be the result of information overload. Ammons and Rivenbark (2008) point out that it is not only the existence of measures but also the ability to tie these measures to management systems that fosters use. We test whether the perceived availability of measures and the linkage of these measures to management processes (via benchmarking, strategic planning, customer service measurement, and linking to budgets) are associated with performance information use.…”
Section: Organizational Factorsmentioning
confidence: 99%
“…Leadership and organizational culture are recurring themes (Broadnax and Conway 2001;Franklin 2000;Moynihan 2005). Radin (2006) points out that some tasks are more compatible with performance management than others, whereas Ammons and Rivenbark (2008) find that the quality of performance data matters.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, government agencies use a variety of performance measurement techniques focusing on costs, quality, impact on service recipients, timeliness, compliance with the laws, fairness, reputation, and customer satisfaction; they collect qualitative and quantitative data, and rely on formal and informal ways of collecting and handling information. Past research found that the so-called higher-order measures, such as efficiency, are more likely to influence management and operation of public organizations rather than the lower-order measures, such as workload and outputs (Ammons and Rivenbark 2008). Thus, our goal is to determine which performance measures (detailed in the methodology section) are more likely to be associated with the more effective accountability relationships in government contracts.…”
Section: Introductionmentioning
confidence: 99%
“…We use crisp set QCA (csQCA) to run the analysis. 1 We also dichotomized condition variables. In this study, we use five condition variables.…”
Section: Qca Resultsmentioning
confidence: 99%
“…Many governments are adopting and implementing performance measurement as a part of reform efforts [34]. Scholars are also investigating the effect of performance measurement [22,27], factors influencing the adoption and use of performance measurement [1,19], and perception of performance measurement in the public sector [16,17].…”
Section: Introductionmentioning
confidence: 99%